Experiencias y percepciones de regulación emocional en practicantes de atención clínica en el Centro de Atención Psicológica de la UAN- Bogotá (2023)
The objective of this research was to analyze the experiences, perceptions and characteristics related to emotional regulation experienced by therapists in training during their clinical practices at the Psychological Care Center - CAP, the topic was approached from a qualitative methodology of descriptive-interpretative scope, with a phenomenological design and an interpretative-hermeneutic approach.